Swimming Research Center Amsterdam
The object of study of the Swimming Research Center Amsterdam is (of course) competitive swimming! What aspecs determine performance in swimming? How does the swimmer adapt to training? How is propulsion generated? Can drag be influenced by technique? What is the optimal training program? All these questions will be interesting for swimmers and coaches who like to excel in competition. From a different perspective these questions are also interesting for the human movement scientist who wants to understand the constraints, control and execution of human movement. On this site you will find some of the answers we found to those questions. Enjoy exploring!